Microplastics as a Trojan horse for trace metals - Hildebrandt, L.; Nack, F.L.; Zimmermann, T.; Pröfrock, D. (Journal of hazardous materials letters, 2021)
[Display omitted] •Small microplastics sorb and release significant amounts of metal and metalloid cations.•Findings highlight the importance of microplastics as a vector for metals and metalloids.•Microplastics might transport toxic metals into the food chain. Due to an assumed lack of anionic binding sites (most plastics are non-polar), scientists long considered virgin particulate plastics inert towards metal ions. However, we proved significant metal sorption to microplastics at neutral pH and release in a solution mimicking gastrointestinal chemistry serving as a proof-of-principle for environmental and human bioavailability. Competitive ion-exchange incubation experiments comprised 55 metals and metalloids. Fast kinetics were observed with 45 %–75 % of As, Be, Bi, Cr, Fe, In, Pb, Th, Sn and the rare-earth element ions being sorbed after 1 h. The investigated metal and metalloid cations showed significant differences in the extent of sorption, based upon which a distinct categorization was possible. Microplastics are not only a potential danger for aquatic and human life, but - as demonstrated in this paper - also serve as a Trojan Horse for dissolved metal cations. The corresponding effects on aquatic and human health will gain higher importance in the near future due to the predicted increases of marine plastic litter and microplastic sorbents.